Pertanggungjawaban Korporasi Dalam Tindak Pidana Perkebunan dan Terhadap Tindak Pidana Korporasi Terhadap Lingkungan Hidup - Edy Prabudy; Tofik Yanuar Chandra; Kristiawanto Kristiawanto (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
In the development of Indonesian criminal law, corporations can be burdened with criminal liability or can be said to be subject to criminal law. Plantation is one sector that is large enough to ensure the welfare of the people. The research method in this article uses qualitative research methods with a normative legal approach or what is known as legal research, which emphasizes the study of library documents related to the problems and objectives of this research. The results of the study state that criminal acts for corporations. Criminal acts can be imposed on corporations and their management and corporations are subject to a maximum fine plus a third.Keywords: Corporate Law; Plantation Law; Environmental law